De-Icing Experience in Lithuania - Daiva Zilioniene; Alfredas Laurinavicius (The Baltic Journal of Road and Bridge Engineering)
With respect to traffic safety Lithuania is a country of increased risk. Thus, in order to ensure traffic safety, it is necessary to maximally reduce the number of accidents, probability of accident risk. The climate in Lithuania is much warmer than the climate of continental regions of the same latitudes. It could be characterised as of average cold, with much snow in winter. In winter traffic conditions are more complicated. When the road pavement is slippery or covered with snow, the accident risk increases. These tasks are solved by winter road maintenance. One of the main objectives of winter maintenance - by removing snow and ice from road pavement and increasing the coefficient of grip between road pavement and tyres - is to reduce accident risk on roads. On slippery road, as soon as unfavourable air and driving conditions appear, the number of accidents increases. At present to prevent road from climatic factors or to eliminate the ice layer from the road surface in a short time is using "Wet salt" technology. An effective acting of the "Wet salt" reveals itself even at -15 °C and the effect could continue up to 12 h after it is spread. However, this is very dependant on weather conditions, change in temperatures, intensity of precipitation and its duration, also traffic volume. On Lithuanian highway Vilnius-Panevezys the analysis of the change in seasonal traffic volume was carried out. To improve winter maintenance of this highway the change in the number of accidents was analysed, depending on the season of the year; also the increase in the number of accidents in winter season was analysed. Investigations of salt, used to minimise road slipperiness, were carried out too. Moisture content %, chlorides content, calculated as natrium chloride % and amount of sulphates % of sodium chloride were investigated. Results of quality investigations of sodium chloride salt, used to reduce road slipperiness, showed that by its chemical composition sodium chloride salt meets very well requirements for the quality of salts used to spread Lithuanian roads, while deviations in the grading of samples taken are not significant.